(untitled) (The Conference Hub, 2025)
This paper examines the pragmatic interpretation and communicative model of sports discourse in English and Uzbek linguistic contexts. Sports language functions as both an information system and a reflection of cultural and emotional expression. The study explores how sports terminology transmits motivation, identity, and cultural nuances across languages, using comparative, cognitive, and linguocultural methods. A communicative model is proposed to demonstrate how pragmatic functions operate in sports contexts, integrating linguistic, cultural, and psychological aspects.